Population-based biomonitoring in the Czech Republic--the system and selected results - Cerná, M; Spĕvácková, V; Cejchanová, M; Benes, B; Rössner, P; Bavorová, H; Ocadlíková, D; Smíd, J; Kubínová, R (The Science of the total environment, 1997)
In the framework of the system of monitoring the environmental impact on population health, the concentration of lead, cadmium and selenium in blood and cadmium in urine was measured in adults (n = 670), children (n = 599) and umbilical blood (n = 549) using atomic absorption spectrophotometry. Furthermore, cytogenetic analysis of peripheral lymphocytes in all population groups under study was investigated. The median blood Pb level for the overall group of adults (47.8 micrograms/l, i.e. 0.23 mumol/1) was significantly higher in men (51.5 micrograms/l, i.e. 0.25 mumol/l). Smoking significantly influenced the blood Pb level in women. The 90th percentile in no group exceeded the value of 100 micrograms/l (0.48 mumol/l). The median blood Cd level in adults (0.9 microgram/l, i.e. 0.008 mumol/l) depends on smoking habit (1.25 micrograms/l, i.e. 0.01 mumol/l). The median urine Cd level was 0.585 microgram/g creatinine (0.59 mumol/mole creatinine) in adults and 0.37 microgram/g creatinine (0.37 mumol/mole creatinine) in children. The median blood Se level (53.5 micrograms/l, i.e. 0.68 mumol/l) was found to be higher in the group of non-smokers (57.5 micrograms/l, i.e 0.73 mumol/l). Lead and selenium level were significantly lower in the umbilical blood. Cytogenetic analysis results showed age-dependent average percentages of aberrant cells: 1.1% in umbilical blood, 1.27% in children and 1.71 in adults in line with the reference values for the Czech population.
Keywords: dospělí; pupečník; Environmental Monitoring; Humans; Data Interpretation, Statistical; surveillance populace; kadmium; Lead; Umbilical Cord; Czech Republic; Cadmium; mužské pohlaví; Česká republika; Age Factors; Adult; Chromosome Aberrations; veřejné zdravotnictví; T-Lymphocytes; Sex Factors; Population Surveillance; olovo; ženské pohlaví; sexuální faktory; věkové faktory; T-lymfocyty; interpretace statistických dat; lidé; selen; dítě; Child; Selenium; Male; Public Health; chromozomální aberace; monitorování životního prostředí; Female